Holistic Scientific Thinking: A New Path to Contemporary Islamic Studies - Fauzian, Rinda (Online Journal of Research in Islamic Studies, 2024)
In the study of contemporary Islam, a holistic scientific thinking approach offers a new perspective that seeks to integrate a variety of disciplines and dimensions of life. This approach focuses not only on separate scientific aspects, but also on the interrelationship between the spiritual, social, political, and economic dimensions of Islam. By combining scientific methods with Islamic values and ethics, holistic scientific thinking becomes relevant to understanding global challenges such as social change, environmental crises, and modern economic dynamics. This research explores the potential of holistic thinking as a new path in a more inclusive and sustainable study of Islam. This approach offers an alternative to the dualistic paradigm that often separates science and religion, thus enabling a renewed understanding of Islam in the context of the modern world.